Balcanistica hungarica rediviva - Nagy, Levente (Zeitschrift für Balkanologie, 2003)
The article is the presentation of the István Schütz’s book: Blank Spots in the Balkan, Balassi Kiadó, Budapest, 2002. The first chapter of the book is devoted to the common vocabulary of the Albanian and Romanian languages, the second it is a ‘condensed’ history of the Balkan region by antiquity from Middle Age. The third chapter of the book deals with the most sensitive issues of the region, the origins of the Albanian, Romanian and Macedonian languages.